Synergistic Effect Between Online Broadcast Media and Interactive Media on Purchase Intention - Gao, Yin; Zhao, Lin (Frontiers in Psychology, 2021)
It is becoming increasingly important for marketers to use online broadcast media and interactive media simultaneously. In this paper, three studies were conducted to explain the mechanism inherent in a synergistic effect. We ran Study 1 to test the synergistic effect of online broadcast media and interactive media on purchase behavior. We conducted Study 2 (synergistic vs. non-synergistic groups) to test the differences between the groups. Study 2 was a 2 (interference vs. no interference terms) × 2 (synergistic vs. non-synergistic groups) experiment to test whether the interaction between online broadcast media and interactive media is a necessary condition for the synergistic effect. Finally, Study 3 was conducted to test the difference in the level of information processing between online broadcast media and interactive media as a necessary condition for the synergistic effect. We designed a 2 (questioning vs. not questioning) × 2 (synergistic vs. non-synergistic groups) experiment to examine the difference between the groups. The results show that online broadcast media and interactive media have a synergistic effect on consumer purchase intention and memory. Study 1 shows that participants in the synergistic group had a higher purchase intention than participants in the non-synergistic group. Study 2 revealed a significant cognition interaction effect on product memory between online broadcast media and interactive media. Finally, in Study 3, the difference in the information processing level between broadcast media and interactive media had a significant synergistic effect on product memory.